Origin and evolution of the archaeo-eukaryotic primase superfamily and related palm-domain proteins: structural insights and new members - Iyer, Lakshminarayan M. (Oxford University Press, 2005)
We report an in-depth computational study of the protein sequences and structures of the superfamily of archaeo-eukaryotic primases (AEPs). This analysis greatly expands the range of diversity of the AEPs and reveals the unique active site shared by all members of this superfamily. In particular, it is shown that eukaryotic nucleo-cytoplasmic large DNA viruses, including poxviruses, asfarviruses, iridoviruses, phycodnaviruses and the mimivirus, encode AEPs of a distinct family, which also includes the herpesvirus primases whose relationship to AEPs has not been recognized previously. Many eukaryotic genomes, including chordates and plants, encode previously uncharacterized homologs of these predicted viral primases, which might be involved in novel DNA repair pathways. At a deeper level of evolutionary connections, structural comparisons indicate that AEPs, the nucleases involved in the initiation of rolling circle replication in plasmids and viruses, and origin-binding domains of papilloma and polyoma viruses evolved from a common ancestral protein that might have been involved in a protein-priming mechanism of initiation of DNA replication. Contextual analysis of multidomain protein architectures and gene neighborhoods in prokaryotes and viruses reveals remarkable parallels between AEPs and the unrelated DnaG-type primases, in particular, tight associations with the same repertoire of helicases. These observations point to a functional equivalence of the two classes of primases, which seem to have repeatedly displaced each other in various extrachromosomal replicons.